FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIFITAS PENGENDALIAN INTERN (PERSEPSI PEGAWAI PADA SKPD SE-KABUPATEN BUTON) - Rais R, Muhammad (JITAA : Journal Of International Taxation, Accounting And Auditing, 2023)
This study aims to determine (1) the effect of auditor quality on the effectiveness of internal control. (2) The effect of audit scope on the effectiveness of internal control (3) The influence of leadership style on the effectiveness of internal control (4) The influence of auditor quality, audit scope, and leadership style simultaneously on the effectiveness of internal control. The data collection method used is field research, library research and questionnaires. The data analysis method used by the author is multiple linear regression analysis. Based on the results of research conducted on the factors that affect the effectiveness of the internal control system in the government sector, it can be concluded as follows: (1) Audit quality has no effect on the effectiveness of internal control. (2) The scope of the audit has no effect on the effectiveness of internal control. (3) Leadership style has an effect on the effectiveness of internal control. (4) Audit quality, audit scope, leadership style together affect the effectiveness of internal control.